Visual comparative analysis of green logistics research at home and abroad based on knowledge map - Ziyu LIU (Journal of Hebei University of Science and Technology, 2020)
In order to explore the focus and direction of green logistics research and providing reference for China′s green logistics research, a comparative analysis of relevant domestic and foreign documents was conducted. Based on 936 domestic and foreign data retrieved from CNKI and Web of Science, the hotspots, evolution paths and cutting-edge technologies of green logistics at home and abroad were analyzed by using the knowledge maps of document co-citation, keyword co-occurrence, clustering, time zone map and mutation words generated by visual software citespaceⅤ. The result shows that the recent and future sustainable hotspots and frontiers in China are in the area of regional green logistics, such as cold chain logistics, tourism logistics, and agricultural product logistics, etc., while foreign countries are specific to supply chains, optimization models, vehicle routes, and fuel consumption. Regarding the research on green logistics, foreign countries focus on innovation and micro level, but domestic studies lay particular emphasis on macro aspects. The research on micro aspects should be strengthened and the process of green logistics should be accelerated by technological innovation in China. The research results are of great significance for analyzing the evolution path of green logistics and the prediction of research frontier, and provide theoretical basis for the follow-up research.